PEMBELAJARAN APRESIASI SASTRA MELALUI PENDEKATAN KOMUNIKATIF BERBASIS KOOPERATIF DAN IMPLIKASINYA TERHADAP PENDIDIKAN KARAKTER - Abdul Salam (UNDAS: Jurnal Hasil Penelitian Bahasa dan Sastra, 2018)
The objective of the study is to find out the literature appreciation learning through communicative approach base on cooperative and its implication towards character building at XII BB class SMKN 3 Banjarbaru. The data collection is done through triangulation using questionnaires, tests, and observation. The results of the study which is analyzed qualitatively and quantitatively shows that the average score of students in analyzing literature before the activity is applied is only 46,61. After conducting the approach, the students’ average score in analyzing the literature work increased into 74,81 in cycle I and 76,81 in cycle II. The implication towards the character building is that the communicative approach based on the cooperative learning in the literature study gives the enforcement to the students’ character. It can be seen by the increasing number of students who achieved B score. In cycle I less than 70% students could achieve B then it increased to 75% in cycle II.